Coming Full Circle: What Happens When Your Class Turns into ‘Real Life’ - Fabian, Sheri; Nicolaou, Zana (Canadian Perspectives on Academic Integrity, 2021)
In this session, we will share some of the results of my experience with remote teaching and academic misconduct in my 200 seat, Introduction to Canadian Criminal Justice System class, which ran from May to Aug 2020 in the School of Criminology at Simon Fraser University. In June 2020, I learned quite by chance, that 41 of 200 students cheated on their midterm celebration of learning (ironically it was on the bonus question worth 1 of 90 marks - they looked up the due date of the quiz on academic integrity). After considerable thought, I decided to use course concepts and applied a restorative justice approach in my response and invited students to reach out and take responsibility. The student response was surprisingly encouraging, and I realized I needed to understand what happened more formally. Accordingly, we developed a study to examine student experiences with my response, how it affected their learning and understanding of course concepts and materials, and their feelings about academic integrity in online courses, especially during a global pandemic. My research assistant, Zana Nicolaou, and I will present findings from the 41 survey responses and 5 interviews that examined these questions. Then we will engage in conversation about how we can shift from conversations about academic misconduct to strategies that help us build a culture of academic integrity.